Determine the solution set of (2x - 5)2 = 11.

Question

Asked 11/25/2014 11:37:07 AM

Updated 11/25/2014 10:15:35 PM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [11/25/2014 10:12:15 PM]

s

2x = 9 + 3

2x = 12

x = 12/2

x = 6

2x^2 - 3x - 5 = 0;

(x + 1)(2x - 5) = 0;

x + 1 = 0; x = -1;

2x - 5 = 0; 2x = 5; x = 5/2

x = {-1, 5/2)

jeifunk|Points 37597|

Neckveu|Points 150|

immortal009|Points 71|

Question

Asked 11/25/2014 11:37:07 AM

Updated 11/25/2014 10:15:35 PM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [11/25/2014 10:12:15 PM]

Rating

8

(2x - 5)^2 = 11

2x - 5 = ± sqrt 11

2x = 5 ± sqrt 11

x = (5 ± sqrt 11)/2

2x - 5 = ± sqrt 11

2x = 5 ± sqrt 11

x = (5 ± sqrt 11)/2

Added 11/25/2014 10:09:41 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/26/2014 1:10:09 AM]

8

(3x + 1)^2 - 100 = 0

(3x + 1)^2 = 100

3x + 1 = 10 or 3x + 1 = -10

3x = 9 or 3x = -11

x = 3 or x = -11/3

The solution set for the equation (3x + 1)^2 - 100 = 0 is {3, -11/3}

(3x + 1)^2 = 100

3x + 1 = 10 or 3x + 1 = -10

3x = 9 or 3x = -11

x = 3 or x = -11/3

The solution set for the equation (3x + 1)^2 - 100 = 0 is {3, -11/3}

Added 11/25/2014 10:10:52 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/25/2014 10:41:35 PM]

8

When the side of a square is doubled, its area is increased to 28 cm^2. The equation that models the problem is (2x)^2 = 28

Added 11/25/2014 10:11:41 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/25/2014 10:42:00 PM]

8

When the side of a square is decreased in length by 1 foot, its area is 8 ft2. The length of a side of the square is 1 + 2. FALSE.

(x - 1)^2 = 8

x - 1 = 2 sqrt 2

x = 1 + 2 sqrt 2

(x - 1)^2 = 8

x - 1 = 2 sqrt 2

x = 1 + 2 sqrt 2

Added 11/25/2014 10:15:35 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/26/2014 1:10:35 AM]

2x^2 - 4x + 6 = 0 is in general form.
True
False

Question

Updated 11/26/2014 1:49:42 AM

1 Answer/Comment

2x^2 - 4x + 6 = 0 is in general form is true .

Added 11/26/2014 1:44:25 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/26/2014 1:49:43 AM], Rated good by andrewpallarca

The graph of y = ax 2 + bx + c is shown below.
Determine the solution set of 0 = ax 2 + bx + c. **Weegy:** The graph of y = ax^2 + bx + c passes through the points (-2, 0), (0, -2), and (2, 0). The solution set of 0 = ax 2 + bx + c is {-2, 2} **User:** Give the values of a, b, and c needed to write the equation's general form.
(5 + x)(5 - x) = 7
A = 1; B = 0; C = -18
A = 25; B = 0; C = -1
A = -1; B = 0; C = 25
**Weegy:** A = 25 **User:** Write the equation 0.3x 2 + 5x - 7 = 0 in general form and then choose the value of "b."
70
50
5 **Weegy:** multiply through by 10 getting:
3x2+50x?70=0
I believe that is the equation in general form, with "proper" coefficient for the x^2 term, if that is true then answer would be 50 **User:** Select all of the following that are quadratic equations.
3x 2 + 5x - 7 = 0
x3 - 2x2 + 1 = 0
2x - 1 = 0
5x 2+ 15x = 0
6x - 1 = 4x + 7
x 2 - 4x = 4x + 7
(More)

Question

Updated 11/26/2014 1:48:58 AM

2 Answers/Comments

(5 + x)(5 - x) = 7

25x + 5x - 5x - x^2 = 7

-x^2 + 25x - 7 = 0

x^2 - 25x + 7 = 0 is the general form and the value of a , b , c is a = 1 , b = - 25 , c = 7 .

25x + 5x - 5x - x^2 = 7

-x^2 + 25x - 7 = 0

x^2 - 25x + 7 = 0 is the general form and the value of a , b , c is a = 1 , b = - 25 , c = 7 .

Added 11/26/2014 1:47:16 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/26/2014 1:56:48 AM]

3x^2 + 5x - 7 = 0 , 5x^2+ 15x = 0 , x^2 - 4x = 4x + 7 are quadratic equations .

Added 11/26/2014 1:48:58 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/26/2014 1:57:49 AM]

Which of the following is the correct factored form of the given equation?
x 2 - x = 6
(x + 3)(x + 2) = 0
(x + 3)(x - 2) = 0
(x - 3)(x + 2) = 0
(x - 3)(x - 2) = 0
**Weegy:** (x - 3)^2 = 0 written in general form is: x^2 - 6x + 9 = 0 Expand (x - 3)^2 = x^2 - 3x - 3x + 9 = x^2 - 6x + 9 **User:** What is the solution set of the following equation?
3x 2 - 6x = 0
{-2, 0}
{0}
{0, 2} **User:** Write the quadratic equation in factored form. Be sure to write the entire equation.
x 2 - 5x - 24 = 0 **User:** Which of the following equations has only one solution?
x 2 + 4x + 4 = 0
x 2 + x = 0
x 2 - 1 = 0 (More)

Question

Not Answered

Updated 11/25/2014 11:50:38 PM

3 Answers/Comments

(x - 3)(x + 2) = 0 is the correct factored form of the given equation of x^2 - x = 6 .

(x - 3)(x + 2) = 0

x^2 - 3x + 2x - 6 = 0

x^2 - x - 6 = 0

x^2 - x = 6 .

(x - 3)(x + 2) = 0

x^2 - 3x + 2x - 6 = 0

x^2 - x - 6 = 0

x^2 - x = 6 .

Added 11/25/2014 11:44:23 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/26/2014 1:18:07 AM], Rated good by andrewpallarca

Write the quadratic equation of x^2 - 5x - 24 = 0 in factored form is (x - 8)(x + 3) = 0 .

x^2 - 5x - 24 = 0

x^2 - 8x + 3x - 8*3 = 0

(x - 8)(x + 3) = 0

x^2 - 5x - 24 = 0

x^2 - 8x + 3x - 8*3 = 0

(x - 8)(x + 3) = 0

Added 11/25/2014 11:47:28 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/26/2014 1:19:19 AM], Rated good by andrewpallarca

The equation of x^2 + 4x + 4 = 0 has only one solution .

x^2 + 4x + 4 = 0

(x + 2)^2 = 0

x + 2 = 0

x = -2 .

x^2 + 4x + 4 = 0

(x + 2)^2 = 0

x + 2 = 0

x = -2 .

Added 11/25/2014 11:49:09 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/26/2014 1:20:23 AM], Rated good by andrewpallarca

Which of the following is the correct factored form of the given equation?
x 2 + 3x - 4 = 0
(x - 1)(x + 4) = 0
(x - 1)(x - 4) = 0
(x + 1)(x - 4) = 0 **Weegy:** The correct factored form of the given equation x^2 + 3x - 4 = 0 is (x - 1)(x + 4) = 0. **User:** olve n3 + 2n2 - 15n = 0 by factoring. **Weegy:** n3 2n2 - 15n = 0 is n (2 n^4-15) = 0.
**User:** What is the solution set of the following equation?
4x 2 - 25 = 0
{±}
{±}
{±5} **User:** What is the solution set of the following equation?
x 2 = x -
{-1, -4}
{1, -4}
{1, 4} **User:** What is the solution set of the following equation?
(2x - 5)(3x + 1) = 0
{-5/2, 1/3}
{-1/3, 5/2}
{-3, 2/5} **User:** Write a quadratic equation in factored form to model the given problem. Be sure to write the entire equation.
The height of a triangle is 4 more than the base, and the area of the triangle is 6 square units. Find the length of the base. Let x = the length of the base. (More)

Question

Not Answered

Updated 11/26/2014 12:14:03 AM

3 Answers/Comments

n^3 + 2n^2 - 15n = 0

n(n^2 + 2n - 15) = 0

n(n + 5)(n - 3) = 0

n = 0

when n + 5 = 0 , n = -5

when n - 3 = 0 , n = 3

So the solutions are n = 0 , n = -5 , or n = 3 .

n(n^2 + 2n - 15) = 0

n(n + 5)(n - 3) = 0

n = 0

when n + 5 = 0 , n = -5

when n - 3 = 0 , n = 3

So the solutions are n = 0 , n = -5 , or n = 3 .

Added 11/25/2014 11:56:18 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/26/2014 1:13:13 AM], Rated good by andrewpallarca

x = 5/2 , or x = -5/2 are the solution set of the following equation of 4x^2 - 25 = 0 4x^2 - 25 = 0 ,

(2x - 5)(2x + 5) = 0,

when 2x - 5 = 0 , x = 5/2 ,

when 2x + 5 = 0 , x = -5/2 .

(2x - 5)(2x + 5) = 0,

when 2x - 5 = 0 , x = 5/2 ,

when 2x + 5 = 0 , x = -5/2 .

Added 11/26/2014 12:00:49 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/26/2014 1:13:53 AM], Rated good by andrewpallarca

The height of a triangle is 4 more than the base, and the area of the triangle is 6 square units. The length of the base is 2. Let x = the length of the base , the height is 4 + x ,

Area = 1/2*x*(4 + x ) = 6 ,

1/2x(4 + x) = 6 ,

x(4 + x) = 12 ,

x^2 + 4x - 12 = 0 ,

(x + 6)(x - 2) = 0 ,

x = -6 , or x = 2 ,

x > 0 , so the length of the base is 2 , the height is 6 .

Area = 1/2*x*(4 + x ) = 6 ,

1/2x(4 + x) = 6 ,

x(4 + x) = 12 ,

x^2 + 4x - 12 = 0 ,

(x + 6)(x - 2) = 0 ,

x = -6 , or x = 2 ,

x > 0 , so the length of the base is 2 , the height is 6 .

Added 11/26/2014 12:13:58 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/26/2014 1:14:38 AM], Rated good by andrewpallarca

34,469,117

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 842 [Total 6715] Ratings 19 Comments 652 Invitations 0 Offline

There are no comments.